The Integrating Sharīʿah Principles into Digital Finance: Implications for Taxing Cryptocurrency Transactions - Tutut Adiningsih (Faculty of Islamic Business and Management, 2025)
This study examines the implementation of tax on cryptocurrency transactions from an Islamic legal perspective. Using a descriptive qualitative approach and secondary data, this research analyzes the alignment between Indonesian crypto tax regulations and the principles of Fiqh al-Mu‘āmalāt and Maqāṣid al-Sharī‘ah in the framework of Technology Acceptance Model. The findings indicate that crypto assets can be categorized as Māl Mutaqawwam, but tax implementation must consider the principles of justice and public benefit. The study recommends the necessity of a comprehensive sharīʿah guidelines for fiscal policies concerning digital assets